Evaluation Of Spheronized Pellets As Potential Matrix Sustained Release Dosage Form - Lee, Bee Cheng (1995)

(untitled)
Satisfactory spherical pellets were successfully· prepared by the process of extrusionlspheronization using the excipient microcrystalline cellulose (IvrCC) as pellet-forming material. Nonetheless, the preparation of acceptable round spheres is highly dependent upon the attainment of an optimal formulation suited for this mcthod or proccssillg. The earlier part of the work has revealed that the MCe pellet system containing the active ingredientdiclofenac sodium generally produced strongly bonded spheroids which remained intact throughout the dissolution test. It may thus be postulated that the pellets behaved as an inert matrix system. Pelet~pelet yang berbentuk sfera telah berjaya disediakan melalui proses ekstrusi/sferonisasi dengan menggunakan mikrokristalin selulosa sebagai bahan pembentuk pelet. Walau bagaimanapun, penyediaan sfera yang baik sang at hc:rr~,HlruJlE kerada remerolehan suatu formulasi optimum yang padan akan proses tersebut. Kajian awal telah menunjukkan bahawa sistem pelet mikrokristalin selulosa yang mengandungi ramuan aktif diclofenac sodium, pada amnya menghasilkan sferoid yang mempunyai ikatan kuat sehingga bentuknya masih kekal semasa proses pemelarutan. Dengan ini, boleh dikatakan bahawa pelet tersebut bertindak sebagai sistem matriks lengai.